Atlas of Sustainable Development Goals 2018 : From World Development Indicators - World Bank (Washington, DC: World Bank, 2018)
The Atlas of Sustainable Development Goals 2018 is a visual guide to the trends, challenges and measurement issues related to each of the 17 Sustainable Development Goals. The Atlas features maps and data visualizations, primarily drawn from World Development Indicators (WDI) - the World Bank’s compilation of internationally comparable statistics about global development and the quality of people’s lives.